2007
DOI: 10.1002/jcp.21009
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin—a mediator of apoptosis?

Abstract: Previously we have demonstrated an apoptosis inducing activity for a rat hepatocyte conditioned medium (CM) presumably mediated by acidic isoferritins. Here, we present support for this assumption since isoferritins purified from different rat hepatocyte CM significantly enhanced the frequency of apoptotic cells in primary rat hepatocytes, an effect completely inhibited by a neutralizing anti-H-ferritin antibody. The apoptosis induction appears to be related to a 43 kDa ferritin subunit contained in the isofer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Ferritin, as an acute phase signaling molecule in tissue repair and regeneration, may stimulate up-regulation of p53 to mediate apoptosis involving Fas (CD95) signaling and intrinsic mitochondrial proapoptotic pathway [3][4][5][6]. In advanced human atheroma lesions where Fas (CD95) signaling is up-regulated [25], and apoptotic macrophage-derived foam cells are rich in ferritin, suggesting that iron-catalysed reaction is involved in apoptosis [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferritin, as an acute phase signaling molecule in tissue repair and regeneration, may stimulate up-regulation of p53 to mediate apoptosis involving Fas (CD95) signaling and intrinsic mitochondrial proapoptotic pathway [3][4][5][6]. In advanced human atheroma lesions where Fas (CD95) signaling is up-regulated [25], and apoptotic macrophage-derived foam cells are rich in ferritin, suggesting that iron-catalysed reaction is involved in apoptosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Its heavy-chain also has enzymatic properties, converting Fe(II) to Fe(III) as iron is internalized and sequestered in the ferritin mineral core. Recently, ferritin has been viewed not only as an iron-storage protein, but is also related to apoptosis [3,4]. Ferritin heavy chain up-regulation by NF-jB inhibits TNFa-induced apoptosis by suppressing reactive oxygen species (ROS) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that ferritin plays a key role in stimulating upregulation of p53 and mediates apoptosis involving Fas (CD95) signalling, as well as addressing the intrinsic mitochondrial proapoptotic pathway in cultured hepatocytes in vitro (Bresgen et al, 2007). Apoptosis causing peripheral T-lymphocyte depletion of pigs during lethal CSFV infection has been shown to be mediated through Fas-Fas ligand interactions (Summerfield et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ferritin may be intimately involved in many important processes related to NASH pathogenesis including inflammation, apoptosis, oxidative stress, lipid transport, and fibrogenesis. Serum ferritin has also recently been shown to be a predictor of mortality in patients with end-stage liver disease (ESLD) both before [25][26][27] and after liver transplant [27,28]. Multicenter studies have shown that hyperferritinemia with ESLD from all etiologies is associated with increased mortality after adjusting for a variety of potential confounding variables [29,30].…”
Section: Relationship Between Serum Ferritin and Fibroscan Values (Fimentioning
confidence: 98%